Sustainability and Marketing Strategies for the Sagita Malay Orchestra in Nganjuk - Maulana, Iqbal Ridho (Universitas Negeri Surabaya, 2025)
Sagita is a very popular music group in Nganjuk. Sagita has a distinctive musical style sets it apart from other dangdut music groups. The fusion of jaranan music and dangdut makes Sagita easily recognizable and beloved by the people of Nganjuk. Therefore, this study aims to discuss the survival strategies of the Sagita Malay Orchestra. This research was conducted using qualitative methods. The study was conducted online via the WhatsApp application using the VideoCall feature, as the interviewees had hectic schedules. Data collection was performed using observation, interviews, and document analysis. Data analysis was carried out through data collection, reduction, and presentation. The results of this study revealed that the Sagita Malay Orchestra employs numerous strategies to maintain its sustainability in Nganjuk. Using social media as a bridge to expand its target market, Sagita has successfully reached audiences in East Java and throughout Indonesia. As a result, a strategy for maintaining sustainability has been formed, including innovations in musical arrangements, the use of social media, collaborations with viral singers, establishing their music labels, improving performance quality, maintaining member solidarity, and finally, evaluation. These strategies are what Sagita has been implementing to support its sustainability up to the present day.